Feasibility study of the Kerinci 350 MW hydro power plant - Budi Sudiarto; M. Muaz Afra Yunardi (International Journal of Applied Power Engineering (IJAPE), 2022)
The demand for electricity is currently growing rapidly. In accordance with the government's policy to optimize the use of renewable energy sources, including water, by constructing a hydroelectric power plant. The study of the potential utilization of the Batang river flow is aimed at how much of the optimum electric power potential there is in the utilization of the Batang Merangin river flow as a hydropower plant. The results of the calculation of the potential for electric power at the Kerinci PLTA show that the optimum electrical power that can be generated is 366.27 MW and the energy produced annually is 1,443.86 GWh. The cash flow of the Kerinci hydropower project consists of technical estimates, revenues, operating and maintenance costs, inflation, taxes, and depreciation. Benefit-cost ratio analysis is calculated according to probable economic conditions during construction and lifetime. The initial investment cost for the Kerinci hydropower plant is around 12,922,000,000,000. The net present value obtained is 423,372,934,373, the internal rate of return is 10.7%, the return on equity is 16.2 years and the benefit-cost ratio is 1.2. The results show that the Kerinci hydropower plant can be built in terms of both technology and money.